Harmoni dan Tantangan Investasi Melalui Dinamika Harga Saham Berdasarkan BI Rate, Inflasi, Nilai Tukar, dan Harga Minyak Dunia Periode 2014-2021 - Michael Tirta; Joshi Maharani Wibowo; Idfi Setyaningrum; Reza Ainul Yaqin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Investment is synonymous with the activity of placing funds in the current period with the expectation of gaining profits in the future, one of which is through the capital market. One intriguing investment activity is Shariah-compliant investment, not limited solely to Muslims; even non-Muslims are interested in investing due to its principled process, providing a sense of tranquility, and enhancing confidence in transactions deemed halal. The determination of Shariah-compliant investments is undoubtedly influenced by macroeconomic factors. Therefore, it is crucial to examine how the BI rate, inflation, exchange rate, and oil prices affect Shariah stock prices. The method employed is explanatory through a multiple regression model with secondary data from the period 2014 to 2021. This study found that the BI rate and oil prices have an impact on Shariah stock prices. A high BI rate can make interest-based investment instruments more attractive than Shariah stocks, resulting in a shift of funds from the stock market to other financial instruments. Meanwhile, oil prices will affect the performance of companies, especially in the energy sector, such as production costs, transportation costs, and other expenses that use energy as a component of their activities.